The Imperative of Upholding Academic Integrity in the Face of Artificial Intelligence Challenges (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Effective scholarly communication, whether oral or written, is inherently challenging. Scientific discourse relies on objective facts rather than subjective opinions. Hence, it necessitates grounding in evidence derived from research, ensuring the arguments presented are objective and supported by factual findings. Generating scholarly information, even in a single sentence, is a laborious process, demanding considerable time, financial resources, and substantial energy. In some instances, continuous or multi-year research is imperative.Nevertheless, technological advancements have revolutionized this landscape. Writing can now be expedited through the use of available artificial intelligence (AI) technologies, ranging from free versions to premium services. For example, Jenni AI functions akin to a "magical assistant," generating text on requested topics. ELICIT AI excels in grid synthesis, ResearchPal automates literature reviews, and others provide various functionalities. This poses a temptation to researchers, making AI a double-edged sword in the realm of publication integrity.
Keywords: scientific writing; artificial intellegence; ChatGPT